5+2(3y-1)=7y+6
estou com dificuldade em equações
Soluções para a tarefa
Respondido por
4
Pela distributiva,podemos resolver essa equação.
Assim temos:
5+2(3y-1)=7y+6
5+6y-2=7y+6
6y-7y=6+2-5
-y=8-5
-y=3
y=-3
Assim temos:
5+2(3y-1)=7y+6
5+6y-2=7y+6
6y-7y=6+2-5
-y=8-5
-y=3
y=-3
Respondido por
2
5+2(3y-1)=7y+6
5+6y-2=7y+6
6y - 7y = 6 + 2 - 5
- y = 3(-1)
y = - 3
Perguntas interessantes
Português,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
Química,
1 ano atrás